The Neurolytic Celiac Plexus Block Efficacy in Patients with Severe, Chronic Upper-abdominal Cancer Pain - Yondonjamts, Byambasuren; Davaasuren, Odontuya; Ganbold, Lundeg (Central Asian Journal of Medical Sciences, 2016)
Objectives: To study of the efficacy of the neurolytic celiac plexus block (NCPB) in patients with severe, chronic upper-abdominal cancer pain in reducing pain score, morphine consumption, side effects of morphine, and improving performance score. Methods: Fifty-six patients with abdominal cancer who suffered chronic, severe pain were enrolled in this study. All patients received a morphine dose of <100mg/day. Patients were divided into 2 groups: group I included patients who received NCPB, group II included patients who used morphine continuously. The patients' pain score, performance status, morphine consumption and morphine-related side effects were recorded at regular two-week intervals with a final follow-up at eight weeks. Results: After the NCPB administration, the pain score, morphine consumption and morphine-related side effects decreased in group I more than in group II (p <0.0001). The physical performance improved in group I more than group II (p<0.001). In group II, pain scores were consistently elevated and patients continued to receive high doses of opioids with inadequate pain control (p <0.001). In group I, morphine-related side effects (nausea, anorexia, and constipation) had lower grades than in group II (p <0.001). Conclusion: NCPB is one of the choices for palliation of severe, chronic upper-abdominal cancer pain.